Impact of institutional interventions for promotion of rice farming in Thrissur district - Sreelakshmi C C (Department of rural banking and finance management, College of cooperation, banking and management, 2014)
Institution is an effective instrument for economic development. Rice being the staple food of Kerala and rice farming as the livelihood of sizeable number of people, deteriorating rice cultivation demands immediate state intervention. Institutional support system for input supply, production process and marketing can positively promote and protect rice farming. The study entitled ‗Impact of institutional interventions for promotion of rice farming in Thrissur District‘ was conducted with the objectives of (a) examining the developmental programmes/ schemes of various governmental and other institutions for the promotion of rice farming in Kerala, (b) analysing the impact of developmental schemes of various institutions on the net income of the farmers and (c) analysing the constraints of rice farmers so as to suggest policy measures for the promotion of rice farming. Ninety respondents consisting of 30 each from three panchayats of Thrissur district viz., Pazhayannur, Adat and Mundathikode were selected as the sample size through multi stage random sampling method. Data were collected through pre-tested structured interview schedule. The critical variables of the study were the institutions and their schemes, various assistance to rice farmers, demographic details of respondents, volume and cost of cultivation, net income, sources and uses of credit, marketing agencies for rice procurement and constraints of rice farming. The major statistical tools used for the study were Chi-square test, Paired t-test, ANOVA test, Post-hoc test for multiple comparison, Cobb-Douglas production function and Mann-Whitney U test. Consultative Group on International Agricultural Research (CGIAR), New York coordinate and cooperate with various countries to promote rice farming at the international level. International Rice Research Institute (IRRI) is the most important rice development institution under CGIAR. Department of Agriculture under Government of India is the pivotal, around which the whole national programmes for rice farming revolves especially Rashtriya Krishi Vikas Yojana (RKVY) with components of High Yielding Variety (HYV) seeds, fertilisers and other assistance to paddy development. Central Rice Research Institute, Cuttack, has contributed remarkably to HYV seeds in rice in the country. Commercial banks have immensely supported the voluminous credit needs of rice farming in the country, especially through Kisan Credit Cards and Interest Subvention Schemes. At the state level, institutions working for rice farming are State Department of Agriculture, Kerala State Civil Supplies Corporation (SUPPLYCO), Co-operative banks and Kerala Agricultural University (KAU). The Minimum Support Price (MSP) for paddy is operated through SUPPLYCO. Cooperatives, in addition to the programmes of State/ local governments, have their own schemes for rice farmers. KAU is a premier institution for rice farmers in the State. Krishi Vigyan Kendras, and Krishi Bhavans are also important institutions engaged in rice development. Agricultural Technology Management Agency (ATMA) is a major non - governmental agency involved in promoting rice farming. Second objective of the study is to measure the impact of institutional interventions on net income of farmers by supporting production, credit and marketing activities. All the respondents availed assistance under RKVY and Sustainable Development of Rice (SDR) schemes for seeds, fertiliser, training and information. It is found that seed component of SDR and RKVY made positive shift among rice farmers to HYVs in cultivation. Paired t-test was employed to analyse the impact of seed subsidy, which is statistically significant at five per cent level. Cobb-Douglas production function used for analysis with gross income as dependent variable and seed, labour, fertiliser and herbicide as independent variables, observed that labour and seeds are important determinants of income. It implies that seed subsidy has promoted rice production. Private agencies like money lenders are also prominent among rice farmers. Commercial banks are found to be providing higher per capita credit to farmers in all the three study areas. Cobb-Douglas production model was fitted by taking total production as a function of Gross Cropped Area and credit. It was noted that credit is a highly significant determinant in production. With respect to marketing, MSP gave confidence to farmers to produce by ensured procurement price and also by stabilising the open market prices. Mann-Whitney U test was used to compare farmers marketing to SUPPLYCO for MSP and to private agencies. Significant difference was found between income of farmers who are supplying their produce to SUPPLYCO and that of supplying to private agencies. Open ended questions were administered to respondents to analyse the third objective of constraints in rice farming. The responses were classified into four categories, viz., (a) production, (b) finance, (c) marketing and (d) institutional constraints. . Lack of availability of skilled labourers, high wage levels and attack of pests and diseases are the most important production problems. Inclusion of rice farming operations under the National Rural Employment Guarantee Programme (NREGP) can reduce the problem of availability of labour and high wage levels. Adoption and practice of IPM techniques can reduce the major production problems of pests, diseases and weed. Lack of availability of timely and adequate credit is the major financial constraint faced by the farmers. Provision of timely interest free loans and interest subsidies, in adequate amounts will attract more farmers to rice farming. In marketing, delay in realisation of cash from sale proceeds to SUPPLYCO is the important problem, which leads to delayed repayment of credit from private agencies at exhorbitant rate of interest. If the system of ‗linking of credit with marketing‘ followed by Adat Service Co-operative Bank is replicated to the other areas, this problem can be solved to a large extent. The convergence of all subsidies for rice cultivation and strengthening of existing paddy development agencies can reduce the institutional constraints. The study reveals that higher positive institutional interventions has led to increase in productivity, reduction in cost of cultivation, increase in net income and easy accessibility to subsidies, interest free loans and marketing facilities, as evident in the case of Adat Service Co-operative Bank. Institutions are instruments of growth. Institutional interventions to support farmers by ways of seed subsidy, MSP and interest subvention have been found to be influencing the net income of farmers positively. The support system has also protected and promoted not only the production and product price but instilled confidence in the minds of farmers and insulated the market against uncertainty. Hence institutions are inalienable input to inspire and insulate the economy. But existing constraints in rice farming showed there are miles to go to provide economic independence to rice farmers.